(untitled) (Journal of Philosophy Culture and Political Science, 2021)
We have 30 years of independence. At the same time, the question arises about the potential of the Kazakh falsafa, what is its current state. Of course, it is known that a lot of research, monographs, and scientific projects are written and published in the field of philosophy. Teachers educate students, defend diplomas, master’s works, and doctoral theses. However, the problems and ideas raised by the Kazakh falsafa, how did they meet the requirements of the time and arouse the interest of students? Is the idea of Mangilik El implemented in our country compatible with the program of modernization of public consciousness? It is obvious that everyone is interested in the question of whether he managed to build his own individual path in World Philosophy. We decided to express our thoughts in this direction. Two large-scale articles by President Kassym-Zhomart Tokayev dedicated to the 175th anniversary of Hakim Abai were popular among citizens. In this article, President says that Abai should become a national brand, and in the second article, he praised Abai as a spiritual reformer. Therefore, in the implementation of the current program of Spiritual Revival, it is important to pay attention to the worldview of Hakim Abai, the deep thoughts behind his remarks. "Abay’s dream is the people’s dream. We should spare no effort to fulfill the dreams and aspirations of the people. Abai’s precepts will lead the new Kazakhstan of the XXI century to such heights. Key words: Kazakh falsehood, Hakim Abay, Mangilik El, Spiritual Revival, value, idea